2019
DOI: 10.1007/s40123-019-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment and Follow-Up in Patients with Severe Chemical Eye Burns

Abstract: Introduction To investigate the demographics, acute management and compliance rates of severe chemical eye burn cases that presented to the largest eye hospital in the United Kingdom (UK). Methods All patients presenting to the Moorfields Eye Hospital emergency department are registered on the electronic patient administration system (PAS). A search of the PAS for patients assigned a preset diagnosis of ‘chemical injury’ was performed for the period from 1 January to 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
3
15
1
Order By: Relevance
“…In the present study, the mean age of the patients was 42.8 ± 12.7 years, which was in agreement with previous studies. Bizrah et al [14] found that the mean age of the patients with mild chemical injuries and severe chemical injuries were 37 ± 22 years and 23 ± 10 years, respectively, which were younger than our study. Men aged 18-64 years [4,10] and children aged 1-2 years [7,15] might be at the highest risk for ocular chemical injury in the workplace or residential locations due to occupational exposure and topical personal products and cleaning agents.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In the present study, the mean age of the patients was 42.8 ± 12.7 years, which was in agreement with previous studies. Bizrah et al [14] found that the mean age of the patients with mild chemical injuries and severe chemical injuries were 37 ± 22 years and 23 ± 10 years, respectively, which were younger than our study. Men aged 18-64 years [4,10] and children aged 1-2 years [7,15] might be at the highest risk for ocular chemical injury in the workplace or residential locations due to occupational exposure and topical personal products and cleaning agents.…”
Section: Discussioncontrasting
confidence: 83%
“…In our study, the majority of the patients were factory workers and construction workers, which was in agreement with the findings of Bizrah and co-workers [16]: most ocular chemical injuries were work-related. Although the delay in the presentation of 133 (83.1%) patients for medical treatment was less than 24 h after injury, only 64 (40.0%) patients were at the consultation room in less than 3 h. Bizrah et al [14] also found that 87% of patients presented to the Moorfields Eye Hospital emergency department within 24 h, but they did not state the numbers of patients in more detailed time window (e.g., less than 3 h, within 3-6 h, within 6-12 h). This suggested that the awareness of prompt treatment should be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Bizrah and coworkers from our same institution reported 10 patients with SOCI identified over 3 months in 2016, of which seven (70%) were attributable to assault. 16 This suggests that the incidence of SOCI continues to increase and that assault-related chemical injuries continue to be a problem, with a similar proportion of assault-related injuries as in our cohort of patients.…”
Section: Discussionsupporting
confidence: 54%
“…13 It will be interesting to see if these legislative changes will translate to a reduced incidence of assault-related SOCI and further studies similar to ours and that of Bizrah and coworkers are advocated. 16 An interesting result from our study is that 40% (10/25) of our patients were lost to follow-up as they DNA subsequent review appointments. This raises several observations.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation